Manajemen Peningkatan Profesionalisme Guru Sekolah Dasar Di Dinas Pendidikan Kabupaten Sarolangun - Yantoro, Yantoro (Jurnal PGSD, 2020)
This research is focused on increasing the professionalism of educators in elementary school teachers in the Sarolangun District Education Office. The purpose of this study was to find out about the management model for improving the professionalism of elementary school teachers in Sarolangun Regency. This research method is a qualitative method that tries to explore and raise all problems and find solutions in accordance with facts and data that is accurate and accurate so that it can be a reference in the management of teacher professionalism improvement in elementary school teachers in Sarolangun Regency. Data collection techniques in this study by (1) interviews; (2) questionnaire (3) documentation study. Informants in this study were officials in the education office involved in basic education, school supervisors, education boards, PGRI, principals and elementary school teachers. The results showed that the management of teacher professional improvement was carried out through three main programs, namely 1) Improvement of teacher qualifications 2) Improvement of teacher competency, 3) improvement of teacher welfare. Planning Planned by recording teacher qualifications, mapping teacher competencies, determining the budget. Implementation is carried out in collaboration with universities, conducting training, MGMP and KKG activities and providing incentives to teachers and providing special allowances for teachers in remote areas, Motiroring and evacuation have not been going well. the absence of the monev team